Jurang Jero Nature Tourism Object in Indonesia: Is it Sustainably Managed? - Daris Fahmaa Sutata; Ronggo Sadono; Muhammad Iqbal Nur Madjid (Department of Forestry, Faculty of Agriculture, University of Lampung, 2026)
Community-based tourism has become an alternative sustainable development strategy that enhances local livelihoods while promoting forest conservation, especially in areas where resource use is limited. This study used a five-dimensional framework, including ecological, economic, social, nature tourism services, and institutional dimensions, to assess the sustainability status of the Jurang Jero Nature Tourism Object’s management. Field observations and respondent interviews were used to gather primary data, which was then analyzed using a rapid appraisal technique for fisheries (Rapfish) modified for Rap-tourism. The results show that management of the Jurang Jero Nature Tourism Object is moderately sustainable, reflecting balanced performance across ecological, economic, social, institutional, and nature tourism service dimensions. Even though the ecological and social dimensions are comparatively strong, more advancements in nature tourism and economic dimensions are required. Improving sustainability and promoting advancement require increased cooperation between stakeholders. Recommended strategies include strengthening human resource capacity through targeted training, developing environmentally sustainable tourism infrastructure, and improving the quality of tourism services and attractions through corporate social responsibility initiatives. Keywords: community-based tourism, leverage analysis, Monte Carlo, National Park, Rapfish